2000
DOI: 10.2337/diacare.23.11.1679
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of triglycerides to HDL cholesterol is an indicator of LDL particle size in patients with type 2 diabetes and normal HDL cholesterol levels.

Abstract: RESULTS -Clinical characteristics, pharmacological therapies, lifestyle, and prevalence of diabetes-related complications were similar in both patient groups. LDL size correlated negatively with plasma triglycerides (TGs) (R 2 = 0.52) and positively with HDL cholesterol (R 2 = 0.14). However, an inverse correlation between the TG-to-HDL cholesterol molar ratio and LDL size was even stronger (R 2 = 0.59). The ratio was Ͼ1.33 in 90% of the patients with small LDL particles (95% CI 79.3-100) and 16.5% of those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0
10

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 30 publications
(34 reference statements)
10
93
0
10
Order By: Relevance
“…The TG and HDL-C ratio has been related to LDL-C size pathophysiology and relevant with regard to the risk of clinical vascular disease. A cut-off value of 1.33 has been reported where >1.33 is suggestive of presence of higher percentage of small LDL particles (14). In our study, this ratio has been found to be 1.00-1.13.…”
Section: Methodssupporting
confidence: 57%
“…The TG and HDL-C ratio has been related to LDL-C size pathophysiology and relevant with regard to the risk of clinical vascular disease. A cut-off value of 1.33 has been reported where >1.33 is suggestive of presence of higher percentage of small LDL particles (14). In our study, this ratio has been found to be 1.00-1.13.…”
Section: Methodssupporting
confidence: 57%
“…Pioglitazone-induced changes in LDL levels also had some variations: a rise in some reports 13,24) , but not in others, including our studies 16,26) (Table 2). In our study, although LDL-C levels were elevated slightly (not statistically significant) in the pioglitazone group, LDL particle size was increased compared to the baseline ( Table 2), as reported previously 27) . LDL particle size, which is associated with increased risk of cardiovascular diseases 28,29) , decreases with progression from normal individuals to overt type 2 diabetes 30) .…”
Section: Discussionsupporting
confidence: 90%
“…TG level and TG/HDL were significantly higher in IFG/IGT but not in iIFG or iIGT compared to NFG/NGT. Increase in TG/HDL is reportedly a good indicator of increase in sdLDL particle [15,16,21]. Hence, the lipid profile in IFG/IGT appears to be very similar to "diabetic dyslipi- demia" in T2DM which is characterized by elevated TG, reduced HDL and predominant presence of sdLDL [3].…”
Section: Discussionmentioning
confidence: 94%